Credit and the housing boom in Malaysia: A comeback? - Daud, SNM; Ahmad, AH; Podivinsky, J (UNIV OVIEDO, 2024)
This article investigates the existence of credit and housing booms in the Malaysian economy, with high levels of household indebtedness. The results reveal that both the credit boom and the housing boom exist and imply the fragility of the financial sector of the economy.